2004
DOI: 10.1086/502380
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Extended-Spectrum Beta-Lactamase–ProducingKlebsiella Pneumoniaein a Neonatal Intensive Care Unit Linked to Artificial Nails

Abstract: Short, well-groomed, natural nails should be mandatory for HCWs with direct patient contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(95 citation statements)
references
References 38 publications
(25 reference statements)
2
86
0
7
Order By: Relevance
“…Notably, NICU 1 had significantly more neonates with low birth weight, performed more surgical procedures, used more NC-CPAP, was more crowded, and experienced outbreaks of Klebsiella pneumoniae and Staphylococcus epidermidis. 15,16 This study was also large enough to allow us to examine risk factors for BSI (after controlling for birth weight) among subgroups of neonates, such as infants with central venous catheters, those with non-CR BSI, and those with BSI caused by gram-positive versus gram-negative organisms. Such subgroup analyses provide more precise estimates of risk, which can be used to guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, NICU 1 had significantly more neonates with low birth weight, performed more surgical procedures, used more NC-CPAP, was more crowded, and experienced outbreaks of Klebsiella pneumoniae and Staphylococcus epidermidis. 15,16 This study was also large enough to allow us to examine risk factors for BSI (after controlling for birth weight) among subgroups of neonates, such as infants with central venous catheters, those with non-CR BSI, and those with BSI caused by gram-positive versus gram-negative organisms. Such subgroup analyses provide more precise estimates of risk, which can be used to guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies of HCP hand carriage have been performed during outbreaks in efforts to detect a potential point source. Outbreaks of Pseudomonas aeruginosa [5,6], extended spectrum β-lactamase-producing Klebsiella pneumoniae [7], and Serratia marcescens [8] have been linked to artificial nails worn by HCP, and molecular epidemiology has confirmed transmission to infants. However, all 4 sites in this current study banned HCP from wearing artificial nails.…”
Section: Discussionmentioning
confidence: 99%
“…159,167,977 In a recent study, multiple logistic regression analysis showed the association of an outbreak of extended-spectrum beta-lactamase-producing K. pneumoniae in a neonatal ICU resulting from exposure to an HCW wearing artificial fingernails. 155 A cluster of five cases of S. marcescens bacteraemia in haemodialysis was associated with a nurse who used an artificial fingernail to open a vial of heparin that was mixed to make a flush solution. The strains isolated from the five patients and the nurse were indistinguishable.…”
Section: Fingernails and Artificial Nailsmentioning
confidence: 99%